FORMULATION AND CHARACTERIZATION OF PERIODONTAL FILMS CONTAINING AZITHROMYCIN AND SERRATIOPEPTIDASE - Rani, Soniya; Singh, Nardev (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present work was to formulate and evaluate periodontal film, which could be capable of delivering therapeutic concentration of azithromycin and serratiopeptidase for a prolonged period of time and could be easily placed into the periodontal pocket. Methods: The films were prepared by solvent casting method using combinations of ethyl cellulose, hydroxypropyl methylcellulose K4M, hydroxypropyl methylcellulose 50 cps, eudragit L-100, and Chitosan in different ratios using dibutyl phthalate as plasticizer. The periodontal films were evaluated for weight variation, thickness, percentage moisture absorption, percentage moisture loss, folding endurance, percentage swelling index, percentage elongation, and in vitro percentage cumulative drug-enzyme release profile. Results: Formulation F12 was found to be a good periodontal film. Hence, it was considered as an optimized formulation. In vitro drug-enzyme release rate studies using keshary-chien diffusion cell showed maximum drug release in F12 formulation (95.92% for azithromycin and 94.20% for serratiopeptidase at the end of 24 h) compared to other formulations. Conclusion: The optimized formulation F12 showed the best drug-enzyme release profile among the others for the preparation of periodontal film. There is a scope for the further study and development of the azithromycin and serratiopeptidase periodontal films.